2012
DOI: 10.2478/v10119-011-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the rare species Eryngium maritimum L. (Apiaceae) in the Gulf of Gdańsk: implications for conservation and management

Abstract: Abstract:We examined the genetic structure and diversity of eight populations of Eryngium maritimum L. (Sea Holly) along 150 km coastline of the Gulf of GdaÒsk in Poland. Allozyme electrophoresis revealed two polymorphic loci among the 31 we tested. The populations showed low levels of genetic diversity (P=6.25, A=1.062, Ht=0.026), with little genetic differentiation between populations (F ST =0.03), although it was statistically significant (p<0.001). The main directions of currents and wind indicate no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The considerable number of individuals with identical genotypes in the two Latvian populations points to a clonal propagation or selffertilisation. Clonal reproduction of the species has been reported in several other studies (Curle et al, 2007;Aviziene et al, 2008;Minasiewicz et al, 2011); however, no studies have reported occurrence of self-fertility in this species. However, because identical genotypes were observed not only within Latvian populations, but also with 8PL and 4EE populations, clonal propagation or self-fertilisation may not be the only interpretation with the low discriminating power of SSAP marker being an alternative explanation for the observed identical genotypes.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…The considerable number of individuals with identical genotypes in the two Latvian populations points to a clonal propagation or selffertilisation. Clonal reproduction of the species has been reported in several other studies (Curle et al, 2007;Aviziene et al, 2008;Minasiewicz et al, 2011); however, no studies have reported occurrence of self-fertility in this species. However, because identical genotypes were observed not only within Latvian populations, but also with 8PL and 4EE populations, clonal propagation or self-fertilisation may not be the only interpretation with the low discriminating power of SSAP marker being an alternative explanation for the observed identical genotypes.…”
Section: Discussionsupporting
confidence: 49%
“…Also, no IBD was observed in E. maritimum populations on the Polish coast (Minasiewicz et al, 2011), which could be related to historical biogeography, as well as to small spatial scale of the study. It can be assumed that populations in Northern Europe are in the evolutionary process of local adaptation after recent recolonisation of northern territories.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the 150 km coastline of the Gulf of Gdańsk, genetic diversity is very low and genetic distance is related to the direction of sea currents influenced by the western winds (Minasiewicz et al . ). Taking the Baltic Coast from Poland to Finland, including the Swedish Islands Gotland and Öland, on the margin of the distribution range in Northern Europe the genetic diversity between and within populations is very low (Ievina et al .…”
Section: Historymentioning
confidence: 97%